Focal psoriasis. - Milano, A. (European Journal of Pediatric Dermatology, 2015)
The involvement of the nail plate reminiscent of trachyonychia, the presence of erythematous and scaling lesions on the palmar and dorsal surface of the hand, the negativity of mycological examinations led us to hypothesize in this child the diagnosis of psoriasis. The lesions affecting only a segment of the skin, from one side only led us to exclude a classical psoriasis; the lesions were not distributed according to the Blaschko lines (1, 2), leading us to rule out the diagnosis of linear psoriasis. We did not find in the handbooks and in the relevant literature similar cases. However, we believe that our patient has a focal psoriasis, similarly to what happens in vitiligo. We intend to monitor the child clinically, to observe the possible appearance of lesions in classical sites that could favor the diagnosis of psoriasis.